The perceptions of African traditional healers and biomedical practitioners towards amafufunyana: healing, prevention and possibilities of mutual collaboration in Hlabisa (KwaZulu-Natal) - Sithole, Simangele Senamile (My University, 2022)
In South Africa, amafufunyana is a condition that is perceived differently across cultural settings. Its conceptualisation differs from time to time and remains contested. From a biomedical perspective, it is seen as a type of mental disorder, while from a traditional healing perspective, it is viewed as a type of spiritual possession that mimics mental disturbance. A qualitative research approach was implemented to guide this study which aimed to explore the perceptions of African traditional healers and biomedical practitioners on amafufunyana by focusing on healing, prevention, and the possibilities of mutual collaboration. Through snowball sampling, five psychiatric nurses, a neuropsychologist and five traditional healers were interviewed telephonically to collect data. Thematic analysis was used as means of analysing data. The findings from this study suggest that the contestation surrounding the condition of amafufunyana emanate from a lack of both medical integration and medical collaboration in healthcare. Context determines the understanding of the different interpretations of amafufunyana by biomedical practitioners and traditional healers and informs their different techniques of healing and prevention. Additionally, both traditional healers and biomedical practitioners indicated their willingness to work together on a conditional basis. By using amafufunyana as an example, this study revisits the challenges to medical integration and suggests the idea of parallel cooperation as an alternative.
A research report submitted in partial fulfilment of the requirement for the Master’s Degree in Sociology to the Faculty of Humanities, University of the Witwatersrand, 2022